Development of nano-satellite - solar energy based power supply system - Htet Aung. (2011)
The objective of this project is to research and develop the energy management system of a nano-satellite, which includes solar energy processing, battery charging system and power conversion system for the satellite. Currently, commercial ready micro-satellite power systems are available but are costly and of fixed specifications that might not meet the requirements of the desired mission. In this project, the power supply system has been developed and tested for various modes of operations. The power supply system built in the project has three main modules: solar array module, battery management module and power distribution module. The solar array module converts sunlight into electricity. The battery management module extracts maximum energy from Solar Array using Perturb & Observe (P&O) based maximum power point tracking (MPPT) algorithm. It also includes battery protection circuit. The power distribution module converts the power from solar array and battery to a well-regulated voltage level and distributes to different subsystems and payloads of the satellite. It also includes current sensing and protection circuits for the payloads. The 8051 microcontroller is used to collect the house keeping data, track the maximum power of the solar array module and communicate with various subsystems. The system is able to supply the loads with voltage level of 3.3V and 5.0V. For the 3.3V output, the voltage ripple and current ripple are 3.56% and 3.12% at full load. Likewise, for the 5V output, the current and voltage ripple are 4.96% and 2.37% at full load. The protection circuit can be tuned to the desired payloads maximum current to protect the payloads. The response time of the protection circuits are about 182.85 µs for 3.3V and 219.94 µs for 5V. To provide fault redundancy, in the event that the 8051 microcontroller is not functioning, the timer IC designed in the system is tuned to give a fixed duty cycle for solar array module. In comparison with other satellites such as The DTUsat by Technological University of Denmark that has a tracking efficiency of only 50% without MPPT, the average tracking efficiency of the designed system is 75% with fixed duty cycle. Furthermore, with the use of MPPT, the average tracking efficiency can reach 87 %. The overall average system efficiency of the designed power subsystem is about 73 %.